ANALISIS PENGARUH SISTEM INFORMASI KEUANGAN DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH: Studi pada Dinas Pemerintahan Kota Semarang - Mardani, Lucki Bighandy; Suhartono, Entot (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2019)
This study aims to determine the influence of regional financial information systems on the quality of local government financial reports and the influence of the government`s internal control system on the quality of local government financial reports on the quality of local government financial reports, This study was conducted at 24 Semarang City Government Offices with a sample of 76 respondents in the section head or financial staff using a purposive sample. Testing data using multiple linear regression analysis. The results of this study show that: regional financial information systems affect the quality of local government financial reports and internal control systems affect the quality of local government financial reports